PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DI DEALER YAMAHA DETA GROUP CABANG MERDEKA BANDUNG - Amalia, Rizki; Aprianti, Ine (Program Studi Manajemen, 2021)
This study was conducted with the aim of knowing the effect of promotion and service quality that affect customer satisfaction at Yamaha Deta Group Dealers, independent branch. The method used in this research is descriptive verification method with a quantitative approach. This study used 98 respondents as research samples using SPSS 26. The instrument used in this study is a questionnaire with 17 questions consisting of two questions each variable. analysis results obtained from the simple linear regression equation hypothesis testing results showed that the results showed that the variables promotion and the quality of service